Clinician-patient communication about cancer treatment misinformation: The Misinformation Response Model - M. Devyn Mullis; Carla L. Fisher; Skyler B. Johnson; Tianshi Liu; Tithi B. Amin; Sherise Rogers; Kennan DeGruccio; Carma L. Bylund (PEC Innovation)
Objective: Cancer treatment misinformation (CTM) is pervasive and impacts patient health outcomes. Cancer clinicians play an essential role in addressing CTM. We previously identified four self-reported responses that characterize the communication process clinicians engage in to address CTM. Clinicians 1) work to understand the misinformation; 2) correct the misinformation through education; 3) advise about future online searches; and 4) preserve the clinician-patient relationship. We sought to confirm and expand on the model we developed by observing cancer clinicians' communication while addressing CTM with a standardized patient (SP). Methods: 17 cancer clinicians were audio recorded in a SP encounter, in which a breast cancer SP asked three questions based on CTM. We thematically analyzed transcriptions of the recordings. Results: Clinicians used four responses with associated strategies and skills to address CTM in a standardized clinical encounter, confirming the previously developed model. The four responses were: (1) work to understand the misinformation; (2) correct the misinformation through education; (3) advise about future online searches; and (4) preserve the clinician-patient relationship. This observational approach allowed us to refine strategies within each response and identify communication skills clinicians enact to address CTM. Conclusion: These findings provide a strong foundation for the Misinformation Response Model for cancer clinicians. Future research should examine which components of the model are most effective in improving patient outcomes. Innovation: This is the first study observing clinicians' communication through simulated practice with SPs about CTM.